Quantification of Ivacaftor, Tezacaftor, Elexacaftor, and Lumacaftor and their active metabolites in plasma using UHPLC-MS/MS: Doors open to the application of therapeutic drug monitoring in cystic fibrosis treatment - Wessels, A. Mireille A.; Elzinga, Femke A.; Koppelman, Gerard H.; Akkerman, Onno W.; Mian, Paola; Touw, Daan J. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2025)
An ultra-high performance liquid chromatography-tandem mass spectrometry method was developed to quantify the cystic fibrosis transmembrane conductance regulator (CFTR) modulators ivacaftor, tezacaftor, elexacaftor, and lumacaftor and their active metabolites hydroxymethyl ivacaftor, tezacaftor M1, and N-desmethylelexacaftor in human EDTA plasma. The analytical method utilized protein precipitation with stable isotope dilution for sample preparation, facilitating a simple and rapid assay, with a total runtime of only 2.1 min. Separation of the seven components and stable isotope-labeled internal standards was achieved on a C18 column, followed by detection using a tandem quadrupole mass spectrometer. Validation of the method was conducted in accordance with the “Bioanalytical Method Validation Guidance for Industry,” of the Food and Drug Administration and with European Medicines Agency's “Guidance on bioanalytical method validation”. The assay covers concentrations ranging from 0.010 to 10 mg/L for ivacaftor, hydroxymethyl ivacaftor and N-desmethylelexacaftor, from 0.025 to 25 mg/L for elexacaftor and tezacaftor, from 0.050 to 50 mg/L for tezacaftor M1 and from 0.100 to 100 mg/L for lumacaftor, using a sample volume of 10 μL. Matrix comparison confirmed the applicability of the assay to human serum and heparin plasma. Stability experiments indicated stability of the CFTR modulators in EDTA plasma over ten days under different conditions. At room temperature, all seven components remained stable for eight days and for ten days in the refrigerator in EDTA plasma and in EDTA whole blood. All seven components were stable in EDTA plasma for ten days in the autosampler after sample preparation and through four freeze-thaw cycles. The developed assay was applied in routine TDM analysis to investigate exposure to elexacaftor, tezacaftor, ivacaftor and their metabolites in people with CF undergoing treatment with Kaftrio®. •The assay for CFTR modulators and its active metabolites uses only 10 μL of sample.•The runtime of the developed UHPLC-MS/MS method is only 2.1 min.•The quantification can be performed in EDTA plasma, serum and heparin plasma.•The UHPLC-MS/MS method is suitable for routine TDM analysis.